Strategi Edukasi Produk Bancassurance AIA Terhadap Keputusan Pembelian Nasabah PT BANK CENTRAL ASIA (Tbk) - Sutrisna, Clarissa Octaviani; Saputro, Arie Hendra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the extent to which bancassurance product education strategies influence customer purchase decisions. Two main variables are evaluated: product knowledge and personal selling, both considered essential in enhancing customer understanding and confidence toward life insurance products offered through banking channels. A quantitative approach was adopted using a survey method involving 30 frontliner staff of PT Bank Central Asia (Tbk), Soekarno Hatta Branch, Bandung, selected through total sampling. Data were collected using a structured questionnaire and analyzed using multiple linear regression. The results indicate that both product knowledge and personal selling positively and significantly affect customers' purchasing decisions. The adjusted coefficient of determination (Adjusted R²) is 0.705, meaning that 70.5% of the variation in purchasing decisions is explained by the two variables. These findings highlight the critical role of effective product education—both through clear product information and persuasive personal interaction—in influencing the decision-making process in bancassurance contexts. This research offers practical implications for financial institutions to design more adaptive and literacy-based communication strategies.